(untitled) (Journal of Advanced College of Engineering and Management, 2023)
The RC-framed building is one of the most common construction technique for seismic-resistant structures due to its ductile nature. However, the seismic performance of RC structures can be significantly influenced by different factors, irregularities being one of the most important aspect. Irregularities on buildings increase the lateral seismic forces and inter-storey drifts thus increasing seismic demands in the structural elements. Due to architectural or functional requirements, many times irregularities cannot be avoided even though such arrangements are discouraged in the building codes including the Nepal National Building Code (NBC) 105:2020. Although many studies have been performed to quantify the effects of such irregularities internationally, design effect has not been analyzed in the context of Nepal and NBC 105:2020. Therefore, this study aims to present the variation in design demand for RC buildings in different irregularities scenarios. Three buildings models exhibiting irregularities in torsion, stiffness, and diaphragm are taken and analyzed in Finite Element platform SAP 2000 and compared with a regular building in terms of storey drift, internal forces, etc. The final design of the structural elements shows that the design demand in terms of section size and reinforcements can be significantly influenced by the presence of such irregularities.